Tested by the Polycrisis: Reforming or Transforming the EU? - Bressanelli, Edoardo (2023)
This thematic issue addresses the question: To what extent have the latest crises—the pandemic crisis and Russia’s war in Ukraine—triggered institutional and policy change in the EU? It contributes to the literature on the impact of crises on integration and the EU political system, presenting new research based on fresh theoretical insights, empirical data, or a combination of both. Theoretically, the contributions collected in the thematic issue explore whether the crises represent a critical juncture for the EU, leading to institutional and/or policy innovations or, rather, set in motion more incremental processes of adaptation. Empirically, all articles—some of which are qualitative, while others are quantitative—are based on original or new data. The first group of contributions deals with institutional change, focusing both on formal (i.e., treaty reform) and informal (i.e., codes of conduct) institutions. A second group moves the focus to policy change, looking at the impact of the Covid-19 pandemic on several policy areas and the energy crisis. Overall, the key lesson is that the EU can now manage and absorb new shocks quite effectively. At the same time, however, it does not promote ambitious and coherent political models or policy paradigms. Instead, it provides room for experimentation through patchwork-like strategies where old and new instruments and settings mix.